Karakterisasi Dan Potensi Pengolahan Air Gambut Menjadi Air Bersih - Ferdy Ashari Syawal; David Andrio; Lita Darmayanti (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2020)
Peatlands could contains water 20 times than it weight. Peat water is brownish red because it cointans high organic substances, therefore peat water should be treating before it can be used as clean water. Adsorption with activated carbon is potential as a method for remove color and organic substances on peat water. This research aims to investigate the characteristics of peat water and analyze the potential treating method for remove color and organic substances on peat water used activated carbon. The result showed color and organic substances on peat water was 1830 Pt/Co and 437,8 mg/L. High adsorption capacity on activated carbon could removed color and organic substance on peat water.Keywords: Peat water, adsorption